1995
DOI: 10.1288/00005537-199508000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine neoplasms of the larynx

Abstract: Neuroendocrine neoplasms of the larynx are a rare group of tumors that include carcinoid tumor, atypical carcinoid tumor, and small cell carcinoma. These neoplasms pose interesting diagnostic, prognostic, and therapeutic dilemmas, and they are, as a whole, aggressive tumors with a tendency for local and distant spread. The authors of this study examined six new cases of laryngeal neuroendocrine neoplasms. One case manifested itself as a primary atypical carcinoid tumor and caused a "carcinoid syndrome." The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 15 publications
2
44
0
Order By: Relevance
“…The cited authors suggested that p53 mutation may be involved in the pathogenesis of atypical carcinoids. 31,3436 Our present patient is also p53-positive.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The cited authors suggested that p53 mutation may be involved in the pathogenesis of atypical carcinoids. 31,3436 Our present patient is also p53-positive.…”
Section: Discussionsupporting
confidence: 59%
“…McCluggage et al (1997) 35 also reported that 3 atypical laryngeal carcinoid patients were p53-positive. Overholt et al (1995) 36 found that 6 of 8 patients with laryngeal neuroendocrine neoplasms (including 2 atypical carcinoids) were p53-positive. The cited authors suggested that p53 mutation may be involved in the pathogenesis of atypical carcinoids.…”
Section: Discussionmentioning
confidence: 99%
“…Atypical carcinoids are locally invasive tumors, although metastases to distant sites and organs have been described [3,7]. The small cell carcinoma is an extremely aggressive malignant tumor that has a biological behavior identical to the small cell carcinoma of the lung [2,9,10]. In general, the paraganglioma is mostly a benign lesion, but despite its histological appearance and biological behavior metastases have been reported [11].…”
Section: Introductionmentioning
confidence: 99%
“…An attempt to control the disease with chemotherapy was unsuccessful, and the patient died after 26 months. 65 The fourth case was in a 64-year-old man with an atypical carcinoid tumor of the larynx involving the surface of the epiglottis with cervical metastases. The patient had carcinoid syndrome (J.…”
mentioning
confidence: 99%